RELATIONSHIP OF PEER INFLUENCE AND FAMILY EATING HABITS ON HEALTHY FOOD CHOICES IN OVERWEIGHT ADOLESCENTS IN SURAKARTA - Khairunnisa Nadya Risti; Eti Poncorini Pamungkasari; Suminah Suminah (Universitas Airlangga, 2021)
Unhealthy eating habits among Indonesian occur not only in adults, but also in adolescents. Adolescence is a transitional period and most easily aff ected by the surrounding environment. Environmental infl uences such as peer infl uence and family eating habits are dominant factors for food they choose to consume. This study aimed at analyzing the relationship of peer infl uence and family eating habits on healthy food choices in overweight adolescents in Surakarta. It used observational study with cross sectional approach. Random sampling was used to determine its samples, consisting of 96 respondents. The data of peer infl uence, family eating habits, and healthy food choices were collected through structured questionnaires. They were analyzed by using the Pearson Product Moment statistical test. The results indicated that there is a relationship between peer infl uence and healthy food choices in overweight adolescents in Surakarta (p = 0.014; r = -0.250); and there is a signifi cant relationship between family eating habits and healthy food choices in overweight adolescents in Surakarta (p = 0.011; r = 0.258).